Invited colloquium: Foreign languages in an age of globalization. (5th June 2013) - Kramsch, Claire
Abstract : With the advent of globalization and the increasingly multilingual and multicultural nature of nations, institutions and classrooms, the fundamental nature of foreign language instruction is changing. Such traditional notions as: 'native speaker', 'target culture', 'standard L2' are becoming problematic with the influx of immigrants to industrialized nation-states, the diversification of accents, and the stratification of language varieties. Foreign language classrooms, too, are becoming less and less homogenous: lacking common points of reference in a common L1, students have to learn the L2 without any common prior cultural or historical context. Caught between the need to impart a skill that will be 'usable' in a variety of global settings and the desire to develop an L2 academic literacy that is specific to a given national culture, foreign language study is challenged to reconcile the local and the global, its national premise and its transnational entailments. This colloquium explored the changing nature of the challenges facing the teaching and learning of foreign languages in an age of global information technologies, global job market, and global migrations. In particular it focused on the notion of the 'foreign' in foreign language education and how globalization has affected this foreignness.